Pediatric obesity: prevention is better than care - Roberta Romanelli; Nicola Cecchi; Maria Grazia Carbone; Michele Dinardo; Giuseppina Gaudino; Emanuele Miraglia del Giudice; Giuseppina Rosaria Umano (BMC, 2020)
Abstract Pediatric obesity is one of the most relevant health issues of the last century. Obesity-related short and long-term consequences are responsible of a large amount of economic cost. In addition, the different therapeutic strategies, such as lifestyle correction, drug, and bariatric surgery have displayed low effectiveness. Considering this evidence, prevention appears to be more promising than treatment in contrasting obesity epidemic. In this review, we summarize obesity pathogenesis with the aim of highlight the main obesity risk factors that can be addressed as target of preventive interventions. Moreover, we report the evidence about effectiveness of different interventions targeting family, school, and community. A multiple-component intervention, addressing different targets and settings, might be desirable, however more studies are needed to confirm long-term efficacy and to direct policy interventions.